Fermentasi Asam Asetat Dari Nira Nipah (Nypa Fruticans) Menggunakan Acetobacter Pasteurianus Dengan Variasi Volume Inokulum Dan Waktu Fermentasi - Triani, Leni; Chairul, Chairul; Yenti, Silvia Reni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The main products are nipah sap which isobtained from not fruit bunches with high sugar concentrations so as to provide an opportunity in the utilization of nipah sap to be acetic acid. Acetic acid can be produced naturally from ingredients containing sugar through fermentation using bacteria. The variation of inoculums acetobacter pasteurianus is 10%,13% and 16% and the time of acetic acid fermentation is 1, 3, 5, 7 and 9 days. The results of the analysis using the Nelson-Somogyi reagent revealed that the initial sugar concentration was 162,97 g/L. time of bioethanol fermentation is 24 hours. The maximum concentration of acetic acid obtained was 27,22 g/L with a pH 0f 3,47 and yield 33,09%. This maximum concentration was obtained on 9 days of acetic acid fermentation at 13% of acetobacter pasteurianus inoculums.Keywords : Acetobacter Pasteurianus, acetic acid, fermentation, inokulum, nipah sap.